A Perioperative Medicine Model for Population Health: An Integrated Approach for an Evolving Clinical Science. (February 2018) - Aronson, Solomon; Westover, Julie; Guinn, Nicole; Setji, Tracy; Wischmeyer, Paul; Gulur, Padma; Hopkins, Thomas; Seyler, Thorsten M.; Lagoo-Deendayalan, Sandhya; Heflin, Mitchell T.; Thompson, Annemarie; Swaminathan, Madhav; et al.
Abstract : Health care delivery in the United States continues to balance on the tight rope that connects its transition from volume to value. Value in economic terms can be defined as the amount something exceeds its commodity price and is determined by extraordinary reputation, quality, and/or service, whereas its destruction can be a consequence of poor management, unfavorable policy, decreased demand, and/or increased competition. Going forward, payment for health care delivery will increasingly be based on services that contribute to improvements in individual and/or population health value, and funds to pay for health care delivery will become increasingly vulnerable to competitive market forces. Therefore, a sustainable population health strategy needs to be comprehensive and thus include perioperative medicine as an essential component of the complete cycle of patient-centered care. We describe a multidisciplinary integrated program to support perioperative medicine services that are integral to a comprehensive population health strategy. Abstract : Supplemental Digital Content is available in the text.Published ahead of print November 30, 2017.